Population-based cohort study on the risk of pneumonia in patients with non-traumatic intracranial haemorrhage who use proton pump inhibitors. Issue 11 (10th November 2014) - Ho, Sai-Wai; Tsai, Ming-Che; Teng, Ying-Hock; Yeh, Ying-Tung; Wang, Yu-Hsun; Yang, Shun-Fa; Yeh, Chao-Bin
Abstract : Objectives: This nationwide cohort study investigated the association between proton pump inhibitor (PPI) usage and the risk of pneumonia in patients with non-traumatic intracranial haemorrhage (ICH). Design: Nationwide population-based cohort study. Setting: Longitudinal Health Insurance Database 2010 (LHID2010) sampled from the Taiwan National Health Insurance Research Database. Participants: 4644 patients with non-traumatic ICH from 2010 to 2011 were identified. Patients aged <18 years and newly diagnosed with non-traumatic ICH complicated with pneumonia during the same admission period were excluded. A total of 2170 participants were eligible for the final analysis. Main outcome measure: Patients using PPIs or not during the study period were tracked to identify the occurrence of any type of pneumonia. Results: The adjusted HR of the risk of pneumonia for ICH patients who used PPIs was 1.61 (95% CI 1.32 to 1.97, p<0.001). The risk of pneumonia was positively associated with the administration of PPIs. We observed a greater risk of pneumonia in patients who used PPIs than in those who did not. Moreover, we observed that the risk of pneumonia in patients who used PPIs was 2.60 and 2.04 (95% CI 2.01 to 3.38, p<0.001; 95% CI 1.34 to 3.10, p<0.001) greater than that in patients who did not use PPIs when the defined daily dose was <30 and 30−60, respectively. Conclusions: The results of this study indicate that the use of PPIs in patients with non-traumatic ICH is associated with an increased risk of pneumonia, and the severity of this risk depends on the defined daily dose. Physicians should exercise caution when prescribing PPIs for patients with non-traumatic ICH.